THE EFFECT OF FERMENTED PAPAYA LEAVES JUICE EXTRACT IN RATIONS ON KAMPUNG HEUS AGE 14-22 WEEKS - I W., Jusnadiartha; Siti, N W.; Ardika, I N. (Jurnal Peternakan Tropika, 2019)
This research aims to find out the effect of administration of fermented papaya leaves juice toward the appearance of local hen age 14-22 weeks. This research was conducted at hencoopsowned by farmers located in Kediri Tabanan, for two months since preparation until period prior to laying eggs. The design being used was group random design (RAK) with 4 treatments and 4 repetition, thus there were 16 trial units. Each trial unit used 3 free-range hens age 14 weeks with body weight range between 713.45-1750 g. Those four treatments were: A) Commercial ration without fermented papaya leaves juice as control, B) commercial ration + 10% fermented papaya leaves juice, C) commercial ration + 20% fermented papaya leaves juice, and D) commercial ration + 30% fermented papaya leaves juice. The effect of fermented papaya leaves juice extract in ration. Variables being observed including ration consumption, drinking water consumption, body weight gain, final body weight and ration conversion (FCR). Result of research showed that the increasing use of fermented papaya leaves juice could decrease ration consumption and increase consumption of drinking water, but statistically not markedly different (P>0.05). In treatment C, body weight gain and final body weight was the highest compared than treatment A, B and D, but statistically not markedly different (P>0.05). From this result of research it can be concluded that the administration of fermented papaya leaves juice in commercial ration from level 10-30% does not have an effect toward ration consumption, drinking water consumption, body weight gain and final body weight. Key words : free-range hen, fermentation juice papaya leaves,appearance.